Nonmuscle Myosin II is Required for Larval Shell Formation in a Patellogastropod - Liu, Xinyu; Huan, Pin; Liu, Baozhong (Frontiers in Cell and Developmental Biology, 2022)
The molecular mechanisms underlying larval shell development in mollusks remain largely elusive. We previously found evident filamentous actin (F-actin) aggregations in the developing shell field of the patellogastropod Lottia goshimai, indicating roles of actomyosin networks in the process. In the present study, we functionally characterized nonmuscle myosin II (NM II), the key molecule in actomyosin networks, in the larval shell development of L. goshimai. Immunostaining revealed general colocalization of phosphorylated NM II and F-actin in the shell field. When inhibiting the phosphorylation of NM II using the specific inhibitor blebbistatin in one- or two-hour periods during shell field morphogenesis (6-8 h post-fertilization, hpf), the larval shell plate was completely lost in the veliger larva (24 hpf). Scanning electron microscopy revealed that the nascent larval shell plate could not be developed in the manipulated larvae (10 hpf). Further investigations revealed that key events in shell field morphogenesis were inhibited by blebbistatin pulses, including invagination of the shell field and cell shape changes and cell rearrangements during shell field morphogenesis. These factors caused the changed morphology of the shell field, despite the roughly retained “rosette” organization. To explore whether the specification of related cells was affected by blebbistatin treatments, we investigated the expression of four potential shell formation genes (bmp2/4, gata2/3, hox1 and engrailed). The four genes did not show evident changes in expression level, indicating unaffected cell specification in the shell field, while the gene expression patterns showed variations according to the altered morphology of the shell field. Together, our results reveal that NM II contributes to the morphogenesis of the shell field and is crucial for the formation of the larval shell plate in L. goshimai. These results add to the knowledge of the mechanisms of molluskan shell development.